Efficiency versus equality in bargaining - Galeotti, Fabio; Montero, Maria; Poulsen, Anders (Oxford University Press, 2018)
We consider how the outcome of bargaining varies with changes in the trade-off between equality, efficiency, and total-earnings maximization. We observe that subjects avoid an equal-earnings outcome if it is Pareto inefficient; a large proportion of bargaining pairs avoid an equal and Pareto efficient outcome in favor of one giving unequal and total-earnings maximizing payoffs, and this proportion increases when unequal outcomes imply larger earnings to one of the players, even though this also implies higher inequality; finally, we document a compromise effect that violates the independence of irrelevant alternatives condition.